2018
DOI: 10.1007/s00590-018-2139-5
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized trial of total synovectomy versus limited synovectomy in primary total knee arthroplasty: evaluation of bleeding, postoperative pain, and quality of life with SF-12 v2

Abstract: Performing a TS in TKA in patients with osteoarthrosis does not result in a relevant lower postoperative pain, or in an improvement in HRQOL, and it does increase the amount of bleeding after the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…The SF‐12 has been used as an outcome measure in clinical trials to evaluate the efficacy of a broad range of interventions for rheumatic conditions, including pharmacological treatment for osteoarthritis of the hip, knee, and hand ; hydrotherapy treatment for osteoarthritis and fibromyalgia ; Tai Chi for hip or knee osteoarthritis ; hand exercises for rheumatoid arthritis ; foot orthoses for rheumatoid arthritis ; self‐management for fibromyalgia ; surgical procedures, eg, total hip arthroplasty and total knee arthroplasty ; and postsurgical rehabilitation (exercise following total knee arthroplasty) .…”
Section: Medical Outcomes Study 12‐item Short Form Health Surveymentioning
confidence: 99%
“…The SF‐12 has been used as an outcome measure in clinical trials to evaluate the efficacy of a broad range of interventions for rheumatic conditions, including pharmacological treatment for osteoarthritis of the hip, knee, and hand ; hydrotherapy treatment for osteoarthritis and fibromyalgia ; Tai Chi for hip or knee osteoarthritis ; hand exercises for rheumatoid arthritis ; foot orthoses for rheumatoid arthritis ; self‐management for fibromyalgia ; surgical procedures, eg, total hip arthroplasty and total knee arthroplasty ; and postsurgical rehabilitation (exercise following total knee arthroplasty) .…”
Section: Medical Outcomes Study 12‐item Short Form Health Surveymentioning
confidence: 99%
“…Three studies [16, 17, 19], including 435 knees, evaluated postoperative pain. Statistical heterogeneity was found in VAS ( I 2 = 95%, P < 0.00001), and a random effects model was applied.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies [15, 16], involving 188 knees, reported complications. A fixed effects model was utilized ( I 2 = 9%, P = 0.30).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations